Ice recrystallisation and melting in ice cream with different proteins levels and subjected to thermal fluctuation. (January 2020) - Lomolino, Giovanna; Zannoni, Stefania; Zabara, Andrada; Da Lio, Matteo; De Iseppi, Alberto
Abstract: Ice cream of high quality has smooth consistency due to ice crystal sizes between 20 and 50 μm, which depends on ice cream formulation and thermal stress during storage. Ice crystals of 3 "traditional" (milk proteins and stabilisers) and 2 vegan (inulin and potato proteins) ice cream formulations were studied using a cold stage microscope under frozen conditions. Samples were observed before and after a temperature fluctuation (cycles of −18 °C and −6 °C for 14 days), and the data obtained compared with the results of a melting test. Results showed that milk proteins and stabilisers conferred structural stability to ice cream, both in terms of small crystal size (20–50 μm) and behaviour during melting, suitable for storage. Ice creams without one of the two constituents or in presence of potato proteins or inulin, showed a crystal size increase; in this case ice creams were for immediate consumption.